Effect of Water Stress on Enzymatic Activity in two Strawberry Cultivars (Fragaria x ananassa) - Ruiz-Saénz, Diana Rocio; Maldonado-Rosales, Miriam Ivonne; García-Nava, Erika Selene; Reyes-Mérida, Aníbal Uriel; Pineda-Santos, Alicia; Sánchez-Valdés, Jair Jesús (REVISTA TERRA LATINOAMERICANA, 2025)
Strawberry (Fragaria x ananassa) is a fruit produced in the central region of Mexico. This crop is af fected by unfavorable climatic conditions such as drought. The aim of this study was to evaluate the ef fect of water stress and its relationship with changes in enzym activity of the antioxidant system in the cultivars ‘Camino Real’ and ‘Cabrillo’ in the Toluca Valley. The experiment was divided into three phases: F0 (initial), F1 (drought phase) – divided into two dif ferent water regimes: a) optimal or control and b) zero regime and F2 (recovery phase), where the zero regime was subsequently re-irrigated to optimal levels. The enzymatic activities of catalase (CAT) and peroxidase (POX) were evaluated, as well as the concentrations of hydrogen peroxide (H2O2) and proline. A randomized design was established, with three replicates and 15 experimental units each one. F0 showed dif ferences in all variables between cultivars. In the zero regime (F1), compared to the control, the ‘Camino Real’ cultivar showed a 36.03% increase in POX activity and a 22.95% decrease in CAT activity, while ‘Cabrillo’ exhibited a 69.43% decrease in POX activity and a 31.26% increase in CAT activity. H2O2 and proline concentrations increased in both cultivars. In F2, no dif ferences in enzymatic activities were found between the cultivars. The determination of enzymes and osmolytes can serve as indicators of strawberry cultivars with drought stress tolerance traits in new geographical regions. It was concluded that the ‘Camino Real’ cultivar exhibited drought tolerance through enzymatic mechanisms, while the ‘Cabrillo’ cultivar demonstrated low tolerance through osmolyte accumulation mechanisms.